2017
DOI: 10.1371/journal.pone.0180513
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific mortality differences in heart failure patients with ischemia receiving cardiac resynchronization therapy

Abstract: BackgroundRecent studies have reported prognosis differences between male and female heart failure patients following cardiac resynchronization therapy (CRT). However, the potential clinical factors that underpin these differences remain to be elucidated.MethodsA meta-analysis was performed to investigate the factors that characterize sex-specific differences following CRT. This analysis involved searching the Medline (Pubmed source) and Embase databases in the period from January 1980 to September 2016.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 82 publications
0
12
1
1
Order By: Relevance
“…7 In addition, women are at risk of specific CHF causes such as peripartum heart disease (gestation diabetes and hypertension, preterm delivery) and, in the case of breast cancer, chemotherapy and radiotherapyinduced cardiomyopathy, associated with the use of anthracyclines and human epidermal growth factor receptor 2 (HER2) monoclonal inhibitors and X-ray locoregional treatment. 4,5 Moreover, in randomised clinical trials women are often underrepresented, 4 so clinicians frequently administer therapies the efficacy of which are not proved in real-life female patients, who are often older, with HFpEF, with different HF aetiology, with different pharmacokinetics, a better response to resynchronisation therapy, 8 a higher incidence of complications after implantable cardioverter defibrillator (ICD) implantation 9 and less orthotopic heart transplantation access. 10 In addition, age at menopause should be considered an important piece of information to acquire, in order to understand better the correct timing of changes in the cardiovascular system due to the progressive reduction in oestrogens 11 that are able to lead to microvessel damage and, ages later, to HFpEF.…”
Section: Peculiarities Of Heart Failure In Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In addition, women are at risk of specific CHF causes such as peripartum heart disease (gestation diabetes and hypertension, preterm delivery) and, in the case of breast cancer, chemotherapy and radiotherapyinduced cardiomyopathy, associated with the use of anthracyclines and human epidermal growth factor receptor 2 (HER2) monoclonal inhibitors and X-ray locoregional treatment. 4,5 Moreover, in randomised clinical trials women are often underrepresented, 4 so clinicians frequently administer therapies the efficacy of which are not proved in real-life female patients, who are often older, with HFpEF, with different HF aetiology, with different pharmacokinetics, a better response to resynchronisation therapy, 8 a higher incidence of complications after implantable cardioverter defibrillator (ICD) implantation 9 and less orthotopic heart transplantation access. 10 In addition, age at menopause should be considered an important piece of information to acquire, in order to understand better the correct timing of changes in the cardiovascular system due to the progressive reduction in oestrogens 11 that are able to lead to microvessel damage and, ages later, to HFpEF.…”
Section: Peculiarities Of Heart Failure In Womenmentioning
confidence: 99%
“…Moreover, in randomised clinical trials women are often underrepresented, 4 so clinicians frequently administer therapies the efficacy of which are not proved in real-life female patients, who are often older, with HFpEF, with different HF aetiology, with different pharmacokinetics, a better response to resynchronisation therapy, 8 a higher incidence of complications after implantable cardioverter defibrillator (ICD) implantation 9 and less orthotopic heart transplantation access. 10 In addition, age at menopause should be considered an important piece of information to acquire, in order to understand better the correct timing of changes in the cardiovascular system due to the progressive reduction in oestrogens 11 that are able to lead to microvessel damage and, ages later, to HFpEF.…”
Section: Peculiarities Of Heart Failure In Womenmentioning
confidence: 99%
“…Our study may have been underpowered in this regard since the percentage of women in the cohort was only 16% ( n = 128). Several previous studies have reported a better treatment response after CRT implantation for women [18, 19]. Female sex was, however, significantly associated with the composite end point of time to death or hospitalization for heart failure, with a lower risk than male sex.…”
Section: Discussionmentioning
confidence: 82%
“…One such tool is the CHA 2 DS 2 -VASc score, a tool developed for finding risk factors for thromboembolic events in patients with atrial fibrillation (AF) [12]. The CHA 2 DS 2 -VASc score consists of common clinical variables that are known for most patients and also happens to overlap some of the known risk factors after CRT implantation [13]. The score is commonly used by clinicians across many specialties, and especially among electrophysiologists who also often manage CRT patients.…”
Section: Introductionmentioning
confidence: 99%
“…Соответственно, при всем многообразии и постоянном совершенствовании видов и методов хирургического лечения пациентов с БСК, и в частности больных ИБС, востребованность этого вида медицинской помощи не имеет ниспадающей динамики, а смертность от этой патологии продолжает удерживать лидирующую позицию среди прочих причин смертности от БСК. В ряде исследований [7][8][9] была показана взаимосвязь клинического течения, исходов медицинских вмешательств и медико-демографических характеристик пациентов кардиологического профиля, что определило актуальность оценки портрета пациента с ИБС, получившего ВМП, поскольку эти данные могут послужить основой для проведения клинико-экономического анализа применяемых медицинских технологий и разработки мероприятий по совершенствованию медицинской и лекарственной помощи.…”
unclassified